The Dynamic Determinants of Human Development in ASEAN: Evidence from the GMM System Model - Etik Umiyati; Faradina Zevaya; Fadwa Rhogib Asfahani (Department of Development Economics, Universitas Sriwijaya, 2025)
Disparities in quality of life between regions and the phenomenon of economic growth that is not always linear with equitable welfare distribution are major challenges in development today. This study examines to analyze the dynamic determinants of the human development index and its implications for regional mobility within the framework of Klassen typology. The observation period spans from 2018 to 2023. Using the System Generalized Method of Moments (GMM) approach to overcome endogeneity issues, this study estimates the impact of economic growth, economic freedom, government effectiveness, and inflation on the HDI. The findings results show that economic growth has a positive and significant effect on the HDI, with the long-run impact being much greater than the short-run impact. This confirms that improvements in quality of life are cumulative and require steady growth. Conversely, economic freedom is found to have a significant negative effect indicating that market liberalization without institutional maturity actually hinders equitable development. Meanwhile, government effectiveness and inflation did not show a significant effect, implying a gap in policy implementation. This study concludes that in order to encourage regional transition towards higher levels of development, policy strategies must focus on long-run economic growth sustainability and strengthening social safety nets before pursuing aggressive market liberalization.